2009
DOI: 10.1200/jco.2009.25.1264
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Clinical Oncology/Oncology Nursing Society Chemotherapy Administration Safety Standards

Abstract: Standardization of care can reduce the risk of errors, increase efficiency, and provide a framework for best practice. In 2008, the American Society of Clinical Oncology (ASCO) and the Oncology Nursing Society (ONS) invited a broad range of stakeholders to create a set of standards for the administration of chemotherapy to adult patients in the outpatient setting. At the close of a full-day structured workshop, 64 draft standards were proposed. After a formal process of electronic voting and conference calls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 25 publications
(5 reference statements)
0
53
0
5
Order By: Relevance
“…Administration of vesicant drugs poses a significant risk associated with many commonly used drugs (Wickham et al, 2006). We found no specific evidence from reviews relating to nursing interventions or approaches to increase safety in ambulatory chemotherapy but there are strong expert recommendations (Jacobson et al, 2009, Wickham et al, 2006, Wengström and Margulies, 2008) (level1 C) and evidence-based recommendations on intravenous drug administration from general settings (level 1 A/B) relating to the safe administration of medication which points to diverse aspects of assessment (including fitness to receive drugs) and technique (including prevention of infection and the treatment and prevention of injury from vesicant drugs) which fall within the scope of nursing practice. Evaluation (before and after) of a multifaceted nurse-led programme designed to increase the quality of care related to chemotherapy-related toxicities (Moore et al, 2008) showed sub optimal care processes at initiation of the project and resulted in improvements in those processes but the study did not report patient outcomes.…”
Section: Safe Medication Administrationmentioning
confidence: 58%
See 1 more Smart Citation
“…Administration of vesicant drugs poses a significant risk associated with many commonly used drugs (Wickham et al, 2006). We found no specific evidence from reviews relating to nursing interventions or approaches to increase safety in ambulatory chemotherapy but there are strong expert recommendations (Jacobson et al, 2009, Wickham et al, 2006, Wengström and Margulies, 2008) (level1 C) and evidence-based recommendations on intravenous drug administration from general settings (level 1 A/B) relating to the safe administration of medication which points to diverse aspects of assessment (including fitness to receive drugs) and technique (including prevention of infection and the treatment and prevention of injury from vesicant drugs) which fall within the scope of nursing practice. Evaluation (before and after) of a multifaceted nurse-led programme designed to increase the quality of care related to chemotherapy-related toxicities (Moore et al, 2008) showed sub optimal care processes at initiation of the project and resulted in improvements in those processes but the study did not report patient outcomes.…”
Section: Safe Medication Administrationmentioning
confidence: 58%
“…Furthermore, the administration process itself is risky requiring skilled assessment of patient fitness and patency of intravenous access (Walsh et al, 2009). Patient education is a key challenge for patients receiving oral medication where a lack of concordance poses a significant risk (Jacobson et al, 2009). Many of the potential impacts of nursing relate to assessment of toxicities (Walsh et al, 2009) and are reflected in other outcomes considered in this review (e.g.…”
Section: Safe Medication Administrationmentioning
confidence: 99%
“…The American Society of Clinical Oncology and Oncology Nursing Society have established chemotherapy administration safety standards for the clinical setting. 83 These procedures need to be implemented in the home setting to assure the patient and family members are safe.…”
Section: Safe Handling Of Antineoplastic Agentsmentioning
confidence: 99%
“…1 Briefly, the development process was led by a Steering Group from ASCO and ONS with previous experience in this project (the present authors). Steering group members formalized the scope of the project (Figure 1), and ASCO staff performed a structured literature search to identify relevant literature.…”
Section: Methodsmentioning
confidence: 99%